The murder inn [large type] - Patterson, James, 1947-; Fox, Candice (Grand Central Publishing, 2024)
"The doors of the Inn at Gloucester are always open to anyone running from trouble or hiding from life. Its owner, former Boston police detective Bill Robinson, welcomes them with no questions asked. Until two strangers arrive for a temporary stay and a longtime resident starts looking over his shoulders. There's another newcomer in town who puts the Inn under surveillance. When the surveillance turns into a series of attacks. Robinson launches an all-out fight to defend his town, his chosen family, and his home."--Page 4 of cover.